High affinity antibody based on a rationally designed hapten and development of a chemiluminescence enzyme immunoassay for quantification of Alternariol in fruit Juice, maize and flour. (15th June 2019) - Yao, Chan-Yuan; Xu, Zhen-Lin; Wang, Hong; Zhu, Fan; Luo, Lin; Yang, Jin-Yi; Sun, Yuan-Ming; Lei, Hong-Tao; Tian, Yuan-Xin; Shen, Yu-Dong
Highlights: A novel hapten was first designed for uniform immune induction effect. A sensitive ciCLEIA method was developed for detecting Alternariol. The detection results for ciCLEIA are consistent with those of HPLC-MS/MS. Abstract: Alternariol (AOH), a secondary metabolites of the genus Alternaria, is a genotoxic mycotoxin. Because the previous "Mannich antigen" for AOH readily underwent unstable induction, a new AOH hapten was designed for inducing a high-quality antibody against AOH using a conjugate of the AOH carboxymethyl derivative with a carrier protein as the immunogen. A competitive indirect chemiluminescence enzyme immunoassay (ciCLEIA) for AOH was optimized and showed good sensitivity (limit of detection 0.068 ng/mL), a linear range (0.11–1.23 ng/mL), and negligible cross-reactivity with analogues. Average rates of recovery from spiked samples (juice and cereal) were between 72.7% and 115.8%, with coefficients of variation <14.3%. Results from ciCLEIA correlated well with those of high-performance liquid chromatography coupled with tandem mass spectrometry, meaning the proposed method might be an effective screening tool for detection of AOH in food samples.